2021
DOI: 10.1007/s11657-021-01038-w
|View full text |Cite
|
Sign up to set email alerts
|

The current situation in the approach to osteoporosis in older adults in Turkey: areas in need of improvement with a model for other populations

Abstract: Purpose The total number of older adults in Turkey is striking, amounting to around 8 million, and this translates into considerably higher numbers of cases of osteoporosis (OP) and fractures in older adults. In this article, we outlined the current situation of OP in older adults in Turkey and investigated the differences between Turkey and a representative developed European country (Belgium), in terms of the screening, diagnosis, and treatment of OP. Our intention in this regard was to identify areas in nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…In another study conducted to identify the prevalence of osteoporosis and risk factors among Turkish women aged 18-49 years, the measurement of bone mineral density levels indicated that 33% of women were osteopenic and that 6.9% of these women were at medium-high risk of developing osteoporosis (Pinar et al, 2017). In studies conducted in Turkey, it is stated that fractures will increase because of the rapid increase in the elderly population and that there is a need for adult education and awareness studies to establish a national fracture record (Bahat et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted to identify the prevalence of osteoporosis and risk factors among Turkish women aged 18-49 years, the measurement of bone mineral density levels indicated that 33% of women were osteopenic and that 6.9% of these women were at medium-high risk of developing osteoporosis (Pinar et al, 2017). In studies conducted in Turkey, it is stated that fractures will increase because of the rapid increase in the elderly population and that there is a need for adult education and awareness studies to establish a national fracture record (Bahat et al, 2021).…”
Section: Introductionmentioning
confidence: 99%